Implementación de tecnologías innovadoras en la Superintendencia de Banca, Seguros y AFPS - Sakuma Carbonel, Igor Hector Jaser (2021)
This report describes my professional career from the experience and goals achieved as an Information Technology professional, mainly as Chief Information Officer (CIO) of the Superintendency of Banking, Insurance and Private Pension Funds Administrators (SBS) of Peru. For this, it is necessary to highlight the profile of a Systems Engineer from the University of Lima, which is recognized by the correct balance between his/her technical and management skills. In this way, graduates have the possibility and the ability to start and develop a professional career taking advantage of our skills and strengths, in different roles offered by information technologies. In my case, I decided to specialize in business management aspects, for which I have presented in this report my experience in the formulation and execution of Digital Transformation projects in the SBS, as well as the perspective of Enterprise Architecture. As CIO and with the support of an excellent team, we have achieved the implementation of initiatives for the use of innovative technologies in the SBS, with the aim of enhancing the analysis capabilities and the decision-making process, thus complying with institutional mandates. In this way, I have highlighted in this report the main efforts made to strengthen the Supervision process, which is a core business process of the Superintendency. This has been and it is a continuous learning and training process, which seeks to develop skills and incorporate new tools not only to solve technological challenges, but also to adequately manage organizational change and available resources. In this sense, management must be governed by a line of conduct in accordance with the ethics of the profession and the public function, in order to fully represent a professional from the University of Lima.